PENERAPAN MODEL PEMBELAJARAN TEAMS GAMES TOURNAMENT (TGT) BERBANTUAN MEDIA GENIALLY BERBASIS GAMIFIKASI TERHADAP MOTIVASI BELAJAR IPS SISWA KELAS V SEKOLAH DASAR - Tahir, Trisnawati; Syamsuddin, Agustan; Quraisy, Hidayah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to determine the effect of the Teams Games Tournament (TGT) learning model assisted by Genially gamification-based media on motivation and learning outcomes of fourth-grade students in an elementary school in Makassar City. The research method used was an experimental design with a nonequivalent control group design. Sampling was done using random sampling techniques, resulting in a sample of 51 students, with 21 students in the experimental group receiving learning through the TGT model assisted by Genially, and 30 students in the control group receiving conventional learning. Data were collected through motivation and learning outcome tests before and after the intervention. Data analysis was conducted using an independent sample t-test to compare learning outcomes between the experimental and control groups before and after the application of the model, and MANOVA to examine the effects on motivation and learning outcomes simultaneously. The results showed a significant difference in the increase in motivation and learning outcomes between the two groups. The experimental group that used the TGT model assisted by Genially showed a more significant increase than the control group in both variables (p < 0.05). These findings confirm that the integration of technology and gamification approaches in learning can enhance student motivation and learning outcomes.